Correlation of Clinicohaematological Parameters in Paediatric Dengue: A Retrospective Study - Ramakrishna Pai Jakribettu; Rekha Boloor; Andrew Thaliath; Sharanya Yesudasan George; Thomas George; Manoj Ponadka Rai; Umran Rafique Sheikh; Kadke Shreedhara Avabratha; Manjeshwar Shrinath Baliga (Journal of Tropical Medicine)
Dengue is one of the arthropod-borne (arbo) viral diseases transmitted by female mosquito Aedes aegypti. Dengue fever has a wide spectrum of clinical presentation ranging from flu-like illness to severe complicated stage of dengue hemorrhagic fever leading to mortality. This was a retrospective study conducted in a tertiary care hospital in Coastal Karnataka, South India, to know the correlation between the clinical presentation and haematological parameters in the paediatric cases presented with dengue symptoms. A total of 163 paediatric cases who presented fever and dengue-like illness were included in the study. Of which, 69 were confirmed dengue patients. Critical analysis showed that there was a significant difference in the haematological parameters like total leucocyte count, percent differential leucocyte count, and platelets count, in the erythrocyte sedimentation rate (P<0.05 to 0.0001). Additionally, when compared to nondengue patients, even the liver function and renal function parameters were significantly deranged (P<0.05 to 0.0001). Stratification based on NS1, IgG, and IgM showed significant alterations in the haematological, hepatic, and renal parameters. With respect to the treatment a small percentage of patients, that is, 8% (4 patients), required platelet transfusion as their counts went below 20,000/μL. Two patients succumbed to their illness while three required ICU stay.